THE CONCEPTION MOTHER ABOUT INFANT FEEDING FROM 0 TO 2 YEARS (Fiep Bulletin - online, 2012)
The study aimed to evaluate the design maternal infant feeding from 0 to 2 years. It is a descriptive approach quantitative and qualitative. We interviewed 27 mothers who performed the queries of C and D of their children at UBS Dr. John Marinaldo of Holland, City of Caraúbas / RN. Quantitative data were analyzed using simple frequency and qualitative light from the theoretical point. Data were collected after approval by the Ethics Committee in Research of the University Potiguar with protocol No. 166/2010, CAAE: 0170.0.052.000-10. In the majority of mothers (33.33%) had incomplete secondary education. But the economic standard, 51.85% had family incomes from 1 to 2 minimum wages. In relation to breastfeeding 81.48% breastfed their children. The aspects of maternal education, working condition of the mother and family income were not associated with the age of introduction of complementary foods, perhaps due to the homogeneity of the study group, which can be considered a major drawback of the study. Of the respondents, 44.44% were aware of the benefits of exclusive breastfeeding until 6 months of age. Regarding the entry of food and dietary restrictions, 74, 07% reported that the introduction of new foods should occur from 6 months and restrict the consumption of foods such as biscuits stuffed in feeding children. Mothers when they were asked if they believed that children considered plump were healthier than those considered lean, 77.77% said no, since fat was not good for health. In the study realized the responsibility of health professionals in promoting guidelines that are appropriate to the realities of families to promote an educational intervention coherent, able to enlighten, inform, educate and change the way of thinking and acting of the mothers are assisted.
Keywords: Food; Child; Mother